Contemporary Research on Agency in Education: A Systematization of Key Concepts and Developments - Sorokin, Pavel S.; Redko, Timofey D. (Voprosy obrazovaniâ, 2024)
The task of developing individual "agency" (autonomy, proactivity, initiative, etc.), in education is widely discussed in scientific and practical circles. To systematize multi-disciplinary research elaborations in the field of "agency" as an umbrella concept, an analysis was carried out using keywords in the main scientific database Scopus. The analysis includes both publications that directly use the concept, and works using other close terms (resistance, autonomy, initiative, etc.). In addition, a sample of scientific publications of researchers, most authoritative in the field of practical educational policy was separately considered. The systematization of the key concepts and constructs was based on four main criteria: 1) the distinction between “agentic” action and intention/perspective, 2) the scale of the action, 3) the strategic/non-strategic nature of the intention/perspective, 4) the universal/local applicability of the concept or construct. The analysis showed a dominating focus on the "agentic perspective" in the discovered works, as well as a focus on micro-level and local manifestations and effects of “agentic” behavior or plans. From the point of view of empirical indicators of "agency" and related concepts, necessity for operationalization of the action-based and "strategic" manifestations of agency are revealed, which raises the question of the fundamental adequacy of the current approaches to measuring a human being dominating in contemporary mainstream of social sciences.